The Relationship of Psychological Flexibility and Self-Efficacy in Medical Students Year 1 Universitas Swadaya Gunung Jati - Fathurrohman, Nabiel; Fachruddin, Duddy; Meidianawaty, R. Vivi (Syntax Literate, 2025)
Background: Self-efficacy tends to decline among first-year university students. Self-efficacy refers to an individual's belief in their ability to manage and complete specific tasks. Psychological flexibility involves a set of skills that individuals use when faced with challenging thoughts, emotions, feelings, or experiences. Aim: To analyze the relationship between psychological flexibility and self-efficacy in first-year medical students at Universitas Swadaya Gunung Jati. Methods: This study used an analytical observational method with a cross-sectional design. Data analysis was conducted using the Spearman correlation test. Measurement instruments used in this study included the Multidimensional Psychological Flexibility Inventory (MPFI) and the General Self-Efficacy Scale (GSES). A total of 172 first-year medical students from Universitas Swadaya Gunung Jati in Cirebon participated as respondents. Results: Based on the statistical analysis using the Spearman correlation test, the results showed a p-value of 0.000 (p < 0.05), indicating a statistically significant relationship between psychological flexibility and self-efficacy. The correlation coefficient (r) = 0.265 indicating a weak but positive correlation. Conclusion: There is a significant positive relationship between psychological flexibility and self-efficacy.